Faktor-Faktor yang Memengaruhi Struktur Modal dengan Ukuran Perusahaan sebagai Variabel Moderasi - Viorenstia Nery; Liana Susanto (Jurnal Ekonomi, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect of profitability, firm age, liquidity, and managerial ownership on capital structure with firm size as a moderating variable in manufacturing sector companies listed on the Indonesia Stock Exchange in 2017-2020. The research sample is 38 manufacturing companies that have been selected by purposive sampling method. The research data was processed by the Eviews12 SV program with the multiple regression analysis method. The results of the study show that firm age and liquidity have a negative and significant effect on capital structure. Profitability and anagerial ownership have no significant effect on capital structure. Firm size cannot moderate the effect of profitability and liquidity on capital structure.